Profit Sharing dan Moral Hazard dalam Penyaluran Dana Pihak Ketiga Bank Umum Syariah di Indonesia - Nasution, Mustafa Edwin; Wiliasih, Ranti (UI Scholars Hub, 2007)
There are two purposes that want to be assessed in this paper. The first purpose is to indicate whether the moral hazard problems are occurred in the Indonesian Sharia Bank (The moral hazard in this paper is the Indirect Moral Hazard which is the negligence of bank in the financing process influencing the moral hazard problems of the debtor in the other side. The second purpose is to assess whether the financing policies in the Sharia Banking are influenced by profit sharing system. The data for assessing this paper are acquired from the monthly financial reports published by Sharia Banks such as BSM and BMI from January 200I to December 2004. The research based on the Error Correction Model in the long term shows that the increasing of allocation ratio of Murabahah to Musyarakah and Mudharabah results the increasing of non performing.financing ratio. It indicates that the moral hazard problems are occurred in BMI. The moral hazard indication demonstrates that bank is both less careful in financing and less incentive in monitoring process. It also demonstrates the weakness of the Sharia bank's operational system in countering the debtor's moral hazard. The Granger Causality Test proves that profit sharing ratio (nisbah) between bank and debtor influences return ratio, however it does not influence financing allocation). On the other hand, financing a/location ratio influences nisbah ratio, furthermore in BSM case, return ratio influences nisbah ratio. This description shows that nisbah ratio is not only an instrument for calculating revenue/return distribution but also an instrument for Sharia bank in synchronizing profit sharing level with the interest rate in conventional bank.